Notulae entomologicae. Vol. LVI - Meinander, Martin (Societas entomologica Helsingforsiensis, 2012)
Kielet saksa, ruotsi, englanti. Hans Silfverberg: Studies on Galerucine genitalia I (Coleoptera, Chrysomelidae), s. 1 -- Litteratur, s. 9 -- Eduard Wagner: Vier neue Miriden (Heteroptera, Miridae) aus den westlichen Mittelmeerraum, s. 10 -- Eitel Lindqvist: Bemerkungen über einige Pachynexnatus-Arten (Hymenoptera, Tenthredinidae), s. 15 -- A. Smetana: New species and remarks on Siberian Quedius (Coleoptera, Staphylinidae), s. 21 -- J. Balfour-Browne: Two new Hydraenidae (Coleoptera, Staphylinoidea) from the Cape Verde Islands, s. 29 -- Colin Johnsson: Coleoptera from North-East Africa. Lathridiidae, s. 31 -- Wolter Hellén: Die Nematinen Finnlands V (Hymenoptera, Tenthredinidae) Gattung Nematus Panzer, s. 33 -- Eitel Lindqvist: Pachynematus clitellatus und einige nahestehende Blattwespen (Hymenoptera, Tenthredinidae), s. 59 -- Harry Krogerus: Ernst Palmén 60 år, s. 58 -- XVIL Nordiske Entomologmote i Bergen 1977, s. 64 -- Seppo Lakovaara, Anssi Saura, Juhani Lokki & Pekka Lankinen: Genic polymorphism in marginal populations of Drosophila, s. 65 -- Torben B. Larsen: The importance of migration to the butterfly faunas of Lebanon, East Jordan, and Egypt (Lepidoptera, Rhopalocera), s. 73 -- Martin Meinander: Coniopterygidae from Africa (Neuroptera), s. 85 -- Rauno Linnavuori: Taxonomical studies on African Coreoidea (Heteroptera), s. 89 -- Walter Hackman 60 år, s. 84 -- Kauri Mikko1a: Nokkosperhosen (Aglais urticae) (Lepidoptera, Nymphalidae) parittelusta ja sukupolvien lukumäärästä, s. 99 -- Juhani Itämies, Pekka Helle & Lasse Hyytinen: Ornithophila metallica (Diptera, Hippoboscidae) a new bird-fly species in Fennoscandia, s. 103 -- Jukka Jalava, Erkki M. Laasonen & Sakari Nenye: Hada skraelingia (Lepidoptera, Noctuidae): finds from Finland and description of genitalia, s. 105 -- Wolter Hellen: Verzeichnis der in den Jahren 1971—1975 für die Fauna Finnlands neuhinzugekommenen Insektenarten, s. 109 -- Miika Vuola & Simo Korpela: Suomen lasisiipisten (Sesiidae) ja puuntuhoojien (Cossidae) ...